Family Experience with Emotional Impact on The Care of Patients with Schizophrenia At Home: A Systematic Literature Review - Jasmiko Kasan; Meidiana Dwidiyanti; Dian Veronika Sakti Kaloeti (Universitas Jenderal Achmad Yani Yogyakarta, 2022)
Background: The emotional impact experienced by families of schizophrenic patients who are treated at home is considered a community mental health problem that does not receive serious attention from health professionals. Families or caregivers who care for schizophrenic patients at home have the risk to experience mental disorders due to the emotional impact they experience.Objective: To review the journal thats comprehensively explain the emotional impact on the family life of schizophrenic patients.Methods: The database in this review are studies in Scopus, Science Direct, Proquest, and EBSCOhost from 2017 to 2022. Critical appraisal in research that appropriate the inclusion criteria be conducted dependently by author and adviser using the CASP ceklist for review.Results: Six articles met the inclusion criteria for review show that families or caregivers of schizophrenic patients are affected emotionally, significantly on their lives especially their mental health. They feel overwhelmed, stressed, frustrated, angry, depressed, and/or anxious, irritable, painful emotions, getting pressured, wanting to end life, showing poor quality of life in terms of physical, emotional, and mental health.Conclusion: Most of family with schizophrenic patien emotionally effected and have the risk for mental disorders.